A STUDY TO ASSESS THE EFFECTIVENESS OF NURSING CARE PROTOCOL ON KNOWLEDGE REGARDING PREVENTION AND MANAGEMENT OF OSTEOPOROSIS AMONG PREMENOPAUSAL WOMEN SELECTED AREA IN ERODE DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Statement of the Problem: “A study to assess the effectiveness of nursing care protocol on knowledge regarding prevention and management of osteoporosis among premenopausal women at selected area in erode district”Objectives: (1) To assess the knowledge among premenopausal women, before and after nursing care protocol regarding prevention and management of osteoporosis among premenopausal women. (2) To implementation and evaluate the effectiveness of nursing care protocol on knowledge regarding prevention and management of osteoporosis among premenopausal women. (3) To find out the association Pre test score between knowledge of premenopausal women regarding prevention and management of osteoporosis among premenopausal women and with their in selected demographical variables